Psychometric Properties of the Turkish Version of the Pain Flexibility Scale for Parents of Children with Cancer. - Kudubes, Aslı Akdeniz; Bektas, Murat (Comprehensive Child & Adolescent Nursing, 2022)
This study aimed to test the validity and reliability of the Pain Flexibility Scale for Turkish parents of children with cancer. The study was carried out on 240 parents of cancer-stricken children between November 2020 and April 2021. The results were tested with validity and reliability analyzers such as factor analysis, Cronbach's alpha, and item-total score analysis. The scale comprised 24 items including three sub-dimensions. The scales explained 56.93% of the total variance. In both exploratory and confirmatory factor tests, the overall factor loading was greater than 0.30. In the confirmatory factor analysis, all the goodness of fit indexes were greater than 0.91, and the root mean square error of approximation was less than 0.08. The Cronbach's alpha coefficient of the scale was 0.88, with Cronbach's alpha values ranging between 0.79 and 0.85 for the subscales. The Pain Flexibility Scale for Parents was found to be a valid and reliable scale for the Turkish population.